Pengaruh knowledge management terhadap kinerja karyawan bagian teknisi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
The purpose of this study was to investigate the Effect of Knowledge Management which consists of Personal Knowledge, Job Procedure, and Technology on the Employee Performance of technicians at Media Nusantara Citra SKY VISION Samarinda. The tool that used for this analysis was multiple linear regressions. Based on the results of multiple linear regressions analysis implied the Knowledge Management variable that consists of Personal Knowledge, Job Procedure, and Technology had a positive effect and significant on the Employee Performance. Based on calculation on correlation of coefficient had indicated the value of 0.615 or 61.50% at the level of coefficient interval from 0.60 to 0.799, then Personal Knowledge, Job Procedure, and Technology have strong relationships on the Employee Performance. The value on determination of coefficient was 0.378 or 37.8%. This implied that independent variables such as Personal Knowledge, Job Procedure, and echnology in this study affect the employee performance amounted 37.8%. While the remaining 62.2% influenced by other variables that were not examined.